Hubungan antara Kualitas Relasi dengan Saudara Kandung dan Kepuasan Hidup pada Dewasa Awal - Nathasa Pravastha Sugianto; Titik Kristiyani (Fakultas Psikologi Universitas Sanata Dharma, 2021)
This study aimed to determine the relationship between quality of sibling relationship and life satisfaction in emerging adulthood. The hypothesis of this study there was a positive and significant relationship between quality of sibling relationship and life satisfaction. The subjects of this study were 296 emerging adulthood aged between 18 to 22 years and who have the status of college student. The data collected by online surveys or google form. The tool used for collecting data was The Life Satisfaction and Quality of Sibling Relationship scale which was arranged by the writer and distributed using Likert scale. The Life Satisfaction scale had a reliability coefficient of 0,918 and Quality of Sibling Relationship scale had a reliability coefficient of 0,875. The data analysis technique in this study used Spearman correlation’s test with SPSS version 23. The result of this study showed that there was a positive and significant relationship between quality of sibling relationship and life satisfaction (r = 0,377, p = 0,000).